2019
DOI: 10.1111/cxo.12877
|View full text |Cite
|
Sign up to set email alerts
|

Aflibercept therapy in eyes with neovascular age‐related macular degeneration and its effect on choroidal thickness

Abstract: Background: The purpose of this study was to investigate changes in best-corrected visual acuity (BCVA), central macular thickness (CMT) and subfoveal choroidal thickness (SCT) after intravitreal aflibercept injections for neovascular age-related macular degeneration (NV-AMD). Methods: Eighty-nine eyes (48 treatment naive, 41 resistant) were included in this prospective study. All patients were treated with three consecutive monthly injections then every two months as required. BCVA, CMT and SCT were recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…They reported a statistically significant decrease in the density of the choriocapillaris during the follow-up period, which was not seen in healthy age-matched controls (Hikichi and Agarie 2019). Similarly, decreased choroidal thickness was measured in neovascular AMD eyes treated with aflibercept or ranibizumab (Adhi et al 2014;Inan et al 2019;Sariyeva Ismayilov et al 2019;Ting et al 2016;Yamazaki et al 2012). Animal studies support the hypothesis that blocking VEGF may lead to choroidal Fig.…”
Section: Effect Of Treatments For Neovascular Amd On the Choroidmentioning
confidence: 89%
“…They reported a statistically significant decrease in the density of the choriocapillaris during the follow-up period, which was not seen in healthy age-matched controls (Hikichi and Agarie 2019). Similarly, decreased choroidal thickness was measured in neovascular AMD eyes treated with aflibercept or ranibizumab (Adhi et al 2014;Inan et al 2019;Sariyeva Ismayilov et al 2019;Ting et al 2016;Yamazaki et al 2012). Animal studies support the hypothesis that blocking VEGF may lead to choroidal Fig.…”
Section: Effect Of Treatments For Neovascular Amd On the Choroidmentioning
confidence: 89%
“…In PBS a remarkable baseline was observed, which indicated that doxorubicin remained in the nanoparticles without release. For instance, cargo delivery was lower than 10% at 24 h. In contrast, cargo release in the presence of lysosomal extract was clearly found as an increase of the doxorubicin fluorescence versus time.…”
Section: Introductionmentioning
confidence: 90%
“…7 It is well known that nanocarriers shape, size and surface charge are the fundamental parameters that determine their behaviour and interaction with biological systems once administered, affecting distribution, stability, circulation time, recognition, cellular uptake, intracellular transport, accumulation and elimination. 10,24 Deep characterization of the systems developed in research laboratories is still an issue, as it results extremely complicated to analyse so many parameters (beyond those already mentioned above, composition, stability and surface coverage with ligands) separately and then establishing relationships between them. Therefore, a detailed understanding of the physico-chemical properties of nanomaterials is essential for the evaluation of their toxicological impact within acceptable pharmaceutical levels.…”
Section: Nanomedicinementioning
confidence: 99%
See 2 more Smart Citations